Qualitative Study of Perinatal Mental Health Services: Experiences and Perspectives of Health Workers and Patients - Evi Diliana Rospia; Dwi Kartika Cahyaningtyas; Siti Mardiyah WD; Cahaya Indah Lestari (EMBRIO: Jurnal Kebidanan, 2023)
The perinatal period is a transitional period that is vulnerable to changes in women's relationships with partners, family, friends, and wider social networks. This study aims to determine how perinatal mental health services are based on the experiences of health workers and patients. This research is qualitative research with a case study design. The informants in this study were 6 informants, namely 2 health workers and 4 patients with a history of perinatal mental health disorders. The instruments used in this study were structured interview guidelines, interviews were conducted in health facilities and patients' homes. Thematic data analysis using the Collaizi protocol. Qualitative data from this study raised six themes, namely "symptoms of perinatal mental health disorders", "causes of perinatal mental health disorders", "management of mental health disorders", "prevention of perinatal mental health disorders", "barriers to perinatal mental health services", and "support". Pregnant, maternity and postpartum women are vulnerable to mental health problems, especially if a woman is faced with family neglect and lack of husband's support during pregnancy. It is important for health workers, especially midwives, to examine women's problems more comprehensively during antenatal care.